Incidence, predictors and prognostic implications of dyspnea at admission among acute coronary syndrome patients without heart failure. (15th February 2020) - Marcus, G.; Shimony, S.; Stein, G.Y.; Matezky, S.; Iakobishvili, Z.; Minha, S.; Fuchs, S.
Abstract: Background: Among patients with stable coronary artery disease, effort-related dyspnea is associated with a larger ischemic territory and worse outcome. Whether dyspnea, not related to heart failure, is also associated with adverse outcome among patients with acute coronary syndromes (ACS) has not been fully elucidated. Methods: We studied ACS patients enrolled in the biennial Acute Coronary Syndrome Israeli Surveys (ACSIS) during 2010–2013 who were classified as Killip 1. A retrospective comparative analysis was performed between patients with chest pain alone (n = 2017) and those with chest pain with dyspnea (n = 417). Results: Patients with dyspnea were older (64.4 ± 13 vs.61.8 ± 12, p < 0.001), more frequently women (81% vs. 75% p < 0.001) and had higher rates of multiple comorbidities. Statistically significant predictors for dyspnea as a presenting symptom were female sex [HR 1.47 (1.11, 1.89)], chronic kidney disease [HR 1.81 (1.30, 2.52)], chronic obstructive pulmonary disease [HR 1.59 (1.045, 2.429)] and angina ≥24 h [HR 1.46 (1.147, 1.86)]. Patients presenting with dyspnea were less likely to undergo primary reperfusion (31% vs. 42%, p < 0.001) and overall coronary intervention (71% vs. 78%, p < 0.001) during their hospitalization. Mortality rates were significantly higher among patients presenting with dyspnea both at 30-day (3% vs. 2%, p = 0.017) and at 1-year follow-up (9% vs. 4%, p < 0.001). Dyspnea was as an independent predictor of 1-year mortality. Conclusion: The presence of dyspnea is frequent and associated with adverse outcome among patients with ACS without signs of heart failure. Early identification of this higher-risk cohort of patients may allow intensifying treatment and careful follow-up may be warranted. Highlights: Most acute coronary syndrome patients have no overt signs of heart failure. Nevertheless, about a fifth of such patients complain about dyspnea. Dyspnea in these patients is an independent predictor of mortality. Recognizing these high-risk patients may allow prompt treatment intensification.